Exon-skipping and mRNA decay in human liver tissue: molecular consequences of pathogenic bile salt export pump mutations - Dröge, Carola; Wenning, Daniel (Scientific reports, 2016)
The bile salt export pump BSEP mediates bile formation. Over 150 BSEP mutations are associated with progressive familial intrahepatic cholestasis type 2 (PFIC-2), with few characterised specifically. We examined liver tissues from two PFIC-2 patients compound heterozygous for the splice-site mutation c.150 + 3A > C and either c.2783_2787dup5 resulting in a frameshift with a premature termination codon (child 1) or p.R832C (child 2). Splicing was analysed with a minigene system and mRNA sequencing from patients’ livers. Protein expression was shown by immunofluorescence. Using the minigene, c.150 + 3A > C causes complete skipping of exon 3. In liver tissue of child 1, c.2783_2787dup5 was found on DNA but not on mRNA level, implying nonsense-mediated mRNA decay (NMD) when c.2783_2787dup5 is present. Still, BSEP protein as well as mRNA with and without exon 3 were detectable and can be assigned to the c.150 + 3A > C allele. Correctly spliced transcripts despite c.150 + 3A > C were also confirmed in liver of child 2. In conclusion, we provide evidence (1) for effective NMD due to a BSEP frameshift mutation and (2) partial exon-skipping due to c.150 + 3A > C. The results illustrate that the extent of exon-skipping depends on the genomic and cellular context and that regulation of splicing may have therapeutic potential.